ETHNO-CULTURAL CODE AS A VALUE-SEMANTIC DOMINANT OF THE SUPPLY CHAIN MANAGEMENT IN MEDIA INDUSTRY - Alefirenko, N. F.; Dekhnich, O. V.; Cheremokhina, D. A.; Yakimova, E. M. (International Journal of Supply Chain Management, 2019)
Abstract- The present article is devoted to the actual problem of identifying supply chain management position in real mass media discourses, as well as the question of determining intra-linguistic and extra-linguistic sources of the synergistic binomial of ethno-linguistic culture. This article examines the cultural code, which is the key to understanding ethno-culture, including the unique value-semantic topics of the people's living space, determining the dominant principles of the world perception. The purpose of the article is to analyze representation of the ethno-cultural code in the artistic and mass media discourses. The methodological basis of the research is interpretation of culture as a semiotic space. Used copyright methods include: value-semantic and lingvo-suggestive. The article presents results of the study of cultural code as a value-semantic dominant of artistic and mass-media texts through a communicative and pragmatic analysis of multi-genre texts for disclosure of features of mentality in a cultural code. The authors come to the conclusion that in the semantic structure of a word it is necessary to single out a special component, â??cultural meaningâ?, which is formed not by a simple set of individual words, but in text space based on their interaction. The value-sense space created by the cultural code is the basis of entire ethnic community, and deconstruction of the value-sense dominant destroys it.